Investigation of Fe content in Cu-Al-Ni Shape Memory Alloys - Canbay, C. Aksu; Unlu, N.; Ozkul, I.; Polat, T.; Sekerci, M.; Aldas, K. (Pleiades Publishing Ltd, 2018)
Polycrystalline Cu-Al-Ni-Fe-based shape memory alloys with different chemical composition were produced in an arc-melting furnace under an argon atmosphere. Homogenized and aged specimens were prepared for multiple analyses. The temperatures of reversible martensitic transformations, namely A (s), A (f), M (s), M (f), A (max) and Delta H enthalpy values were determined by a DSC device. The phase transition analysis from the room temperature to 850A degrees C was undertaken by DTA. To characterize the lattice structure, an XRD analysis was conducted, the results of which were confirmed by microstructure images obtained from optical microscope observations.
Keywords: Cu Al Mn Fe; DSC; XRD; DTA; shape memory alloys